Multilayer block copolymer meshes by orthogonal self-assembly - Amir Tavakkoli K. G. (Nature Portfolio, 2016)
Block copolymer self-assembly can successfully generate monolayers of complex nanopatterns. Here, the authors orthogonally self-assemble 2 or 3 layers of distinct molecular weight block copolymers, and fabricate complex nanomesh structures without alignment or high-resolution lithographic templating.